Coastal Hazards - Finkl, Charles W.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book covers the gamut of coastal hazards that result from short-term low-frequency events and have high-magnitude and far-reaching impacts on coastal zones the world over. Much of the world$1 (Bs population now lives in low-lying coastal zones that are inherently vulnerable to natural hazards such as flooding from hurricanes, tropical storms and northeastern storm surges; shoreline (beach and dune) erosion; cliff and bluff failures; and saltwater intrusion in coastal aquifers used for drinking water supplies. In addition to the usual range of hydrometeorological disasters in coastal zones, this book covers tsunami impacts and warning systems as well as global perspectives of sea-level rise impacts and human perceptions of potential vulnerabilities resulting from rip currents that cause many drownings each year on beaches. Today, the use of numerical models that help predict vulnerabilities and provide a basis for shore protection measures is important in modern scientific and engineering systems. Final considerations focus on human actions in the form of the urbanization and industrialization of the coast, shore protection measures, and indicate how environmental degradation around coastal conurbations exacerbates the potential for unwanted impacts. Strategies for environmental management in coastal zones, from low-lying wetlands to high cliffs and rocky promontories, are highlighted as a means of living in harmony with Nature and not trying to conquer it.s
Part I: Environmental and Human-Induced Hazards -- The Southeast Florida Coastal Zone (SFCZ): A Cascade of Natural, Biological, and Human-Induced Hazards -- Part II: Remote Sensing of Coastal Hazards (Platforms, Methods, and Procedures) -- Remote Sensing of Coastal Hazards -- Determination of Human Induced Coastal Changes Using RS, GIS, and Geostatistics -- Part III: Flood Hazards (Storm Surge, Sea-Level Rise, and Populations from Risk of Coastal Flood Hazards) -- Coastal Risk versus Vulnerability in an Uncertain Sea Level Future -- Sea-Level Rise Impacts and Responses: A Continental Perspective -- Estimating the United States Population at Risk from Coastal Flood-Related Hazards -- Public Perception of Coastal Hazards from Hurricane Surge -- Anthropogenic Amplification of Storm Surge Damage in the 1935 (3z(BLabor Day(3y (BHurricane -- Coastal Flooding Hazard in Low-Tide and High-Tide Coasts: Evidence from the North Aegean Coast Sea Level Rise -- Part IV: Hydrologic (Groundwater, Saltwater Intrusion, Brine Disposal) Hazards -- Conceptualizing Seawater Intrusion Processes in Small Tropical Island via Geochemical Modelling -- Reducing the Risk Associated to Desalinization Brine Disposal on the Coastal Areas of the Red Sea -- Part V: Coastal Erosion and Sedimentation (Detection and Measurement of Shoreline Retreat) -- Beach Erosion: Causes and Stabilization -- Innovative Technique of Predicting Shoreline Change in Developing Countries: Case of Accra Erosion and Causal Factors -- Detection of Coastal Change by Geo-Informatics Means -- Spatial and Numerical Methodologies on Coastal Erosion and Flooding Risk Assessment -- Coastal Erosion and Protection Policies in Europe: From Eu Programme (Eurosion and Interreg Projects) to Local Management -- Part VI: Coastal Dune Hazards (Erosion and Management) -- Coastal Dune Hazards Erosion and Management in Coastal Dunes -- Part VII: Coastal Storms (Tropical Cyclones and Extra-Tropical Winter Storms) -- Coastal Hazards from Tropical Cyclones and Extratropical Winter Storms Based on Holocene Storm Chronologies -- U.S. Pacific Northwest Coastal Hazards: Tectonic and Climate Controls -- Part VIII: Wave Hazards (Extreme Coastal Waves, Storm Surge, and Runup) -- Extreme Coastal Waves, Ocean Surges and Wave Runup -- Effects of Stratification on Multi-Layered Tsunami Waves -- Part IX: Coastal Marine Pollution -- The Hazards of Beach Litter -- Coastal Hazards from Oil Spills -- Part X: Beach Safety -- Rip Currents.s
Keywords: Geography; Geology; Physical geography; Earth Sciences; Natural Hazards; Coastal Sciences; Physical Geography